EFFECTIVE STRATEGIES IN MANAGING DEMAND AND PRODUCTION CAPACITY OF SERVICES MSMEs IN BEKASI CITY - Sumarsid, Sumarsid (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The Indonesian economy can benefit from the existence of MSMEs, but there are also shortcomings or problems with them, such as the low income limit owned by businesses, a small number of Human Resources (HR), and low levels of education and digital literacy. This research aims to explore demand patterns and production capacity at Ameera Salon, an MSME in Indonesia. We use qualitative methods by collecting data through observation and documentation. Through this research, we realize that the Indonesian economy can benefit from the existence of MSMEs, but is also faced with a number of problems such as low income, limited human resources, and low levels of education and digital literacy. In this situation, the most strategic approach to overcoming the problem of poverty is through the development of MSMEs. However, in handling requests, each type of business needs to consider and analyze the requests in an appropriate manner. This research provides insight into how MSMEs such as Ameera Salon can manage their demand and production capacity. Keywords: Production Capacity, Demand, MSMEs